﻿Serum monitoring of carbamazepine in patients with epilepsy and clinical implications - Angel T. Alvarado; Gustavo Paredes; Gregoriana García; Alexis Morales; Ana María Muñoz; María Saravia; Ricardo Losno; María R. Bendezú; Haydee Chávez; Jorge A. García; Mario Pineda; Luis Sullón-Dextre (Pensoft Publishers, 2022)
Carbamazepine is a drug with a narrow therapeutic range that requires clinical monitoring, since its toxic effects are not easily predictable, and the therapeutic level can vary. Our study aimed to monitor the serum level and determine the concentration/dose relationship of carbamazepine in people with epilepsy, analyzing its clinical implication. It is observed that 90.48% of the study volunteers present serum level values (4.3-10.4 mg/L) within the therapeutic range (4-12 mg/L); 7.14% present supratherapeutic levels (12.7-14.4 mg/L), 2.38% subtherapeutic (0.93 mg/L). The findings indicate a negative correlation (r = -0.616; r2 = 0.379; p = 0.001), between the dose (mg/day) and the dose ratio (mg/L/mg/day); and a positive correlation (r = 0.544; r2 = 0.296; p = 0.002), between the dose (mg/day)-serum concentration (mg/L). ANOVA and Tukey's test mean difference is significant (p<0.05). It is concluded that there is a positive and significant linear correlation between daily doses and serum carbamazepine concentrations, which should be considered to individualize the dose and optimize clinical results.